Contribution of neuroblastoma-derived exosomes to the production of pro-tumorigenic signals by bone marrow mesenchymal stromal cells. Issue 1 (1st December 2017) - Nakata, Rie; Shimada, Hiroyuki; Fernandez, G. Esteban; Fanter, Rob; Fabbri, Muller; Malvar, Jemily; Zimmermann, Pascale; DeClerck, Yves A.
ABSTRACT: The bone marrow (BM) niche is a microenvironment promoting survival, dormancy and therapeutic resistance in tumor cells. Central to this function are mesenchymal stromal cells (MSCs). Here, using neuroblastoma (NB) as a model, we demonstrate that NB cells release an extracellular vesicle (EVs) whose protein cargo is enriched in exosomal proteins but lacks cytokines and chemokines. Using three different purification methods, we then demonstrate that NB-derived exosomes were captured by MSCs and induced the production of pro-tumorigenic cytokines and chemokines, including interleukin-6 (IL-6), IL-8/CXCL8, vascular endothelial cell growth factor and monocyte-chemotactic protein-1, with exosomes prepared by size exclusion chromatography having the highest activity. We found no correlation between the IL-6 and IL-8/CXCL8 stimulatory activity of exosomes from eight NB cell lines and their origin, degree of MYCN amplification, drug resistance and disease status. We then demonstrate that the uptake of NB exosomes by MSCs was associated with a rapid increase in ERK1/2 and AKT activation, and that blocking ERK1/2 but not AKT activation inhibited the IL-6 and IL-8/CXCL8 production by MSCs without affecting exosome uptake. Thus, we describe a new mechanism by which NB cells induce in MSCs an inflammatory reaction that contributes to a favorable microenvironment in the BM.